Comparison of the Effectiveness of 5 IU Oxytocin Bolus and 20 IU Infusion on Uterine Contraction and Hemodynamic Response in Caesarean Section - Fitrisyah, Aidyl; Rose Mafiana; Agustina Br Haloho; Theodorus (Biomedical Journal of Indonesia, 2021)
Uterine atonic can result in postpartum hemorrhage, gravid hysterectomy andmaternal mortality. Oxytocin is the most commonly used agent for the preventionand treatment of atonic uterine during cesarean section. However, the provision ofrapid and increasing the dose may result in hemodynamic instability, cardiovascularcollapse, and death. This study aimed to compare the effectiveness of oxytocin bolus5 IU and oxytocin infusion 20 IU to contractions of the uterus and the hemodynamicresponse in cesarean section with spinal anesthesia.An experimental study, Randomized Controlled Trial (RCT) was conducted in theoperating room Mohammad Hoesin Hospital Palembang from July to August 2016.It was obtained a 44 pregnant at term women who will do a cesarean section thatmeet the inclusion and exclusion criteria. The frequency and distribution of data aredescribed in tables and comparisons between the two groups were analyzed usingSPSS.Of the 44 pregnant women at term, 22 women in the group of oxytocin bolus 5 IUand 22 women in the group of oxytocin infusion 20 IU. By statistical analysis, therewas no significant hemodynamic changes after bolus administration of oxytocin 5 IUor oxytocin infusion 20 IU (p> 0.05) and there were no significant hemodynamicdifferences between oxytocin bolus 5 IU and infusion of 20 IU oxytocin (p> 0.05). Inaddition, there are significant changes in uterine contractions after bolusadministration of oxytocin 5 IU or oxytocin infusion 20 IU (p< 0.05) and there weresignificant differences in uterine contraction in the 3rd minute (p = 0.006), 6thminute ( p = 0.010) and 9th minute (p = 0.008) between oxytocin bolus 5 IU andinfusion of oxytocin 20 IU.It can be concluded that there is no significant hemodynamic changes afteradministration of oxytocin 5 IU bolus and oxytocin infusion 20 IU and there aredifferences in uterine contractions significantly in the 3rd minute, 6th minute and9th minute between oxytocin bolus 5 IU and oxytocin infusion 20 IU.